Evaluation Index System Construction of High-Quality Development of Chinese Real Enterprises Based on Factor Analysis and AHP - Jiawei Wang; Xiaoxuan Gao; Ruhai Jia; Lisan Zhao (Discrete Dynamics in Nature and Society)
China’s economic development has shifted from high-speed to high-quality. The fundamental of promoting the high-quality development of the real economy lies in real enterprises. Therefore, it is urgent to measure the high-quality development of real enterprises scientifically and reasonably. Herein, we construct a comprehensive evaluation index system for the high-quality development of real enterprises based on the existing research and combined with the characteristics of real enterprises. Then, the high-quality development index for real enterprises is created using factor analysis and AHP. Moreover, we measure and analyze the high-quality development of real enterprises in 2020. The results show that the high-quality development level of Chinese real enterprises remains to be further upgraded. Meanwhile, there are obvious contrasts in the high-quality development index of real enterprises in industries and regions. Finally, we put forward some related policy recommendations, such as enhancing policy relevance, insisting on innovative development, and increasing financial sustainability.